Usability and acceptability of ambulatory monitoring in undiagnosed syncope: insights from the ASPIRED-Q qualitative study - Matthew James Reed; Coral L Hanson; Lis Neubeck; Caroline Blackstock; Ellise Clarke; Alice Pearsons (BMJ Open)
Objectives The aim of this study, which was embedded into the ASPIRED randomised controlled trial (ISRCTN10278811), was to explore patient and healthcare professional usability and acceptability of an enhanced (14-day) ambulatory ECG monitoring patch to manage and facilitate discharge of emergency department patients with unexplained syncope.Design A qualitative study using semistructured interviews. Data were analysed using thematic analysis and mapped using the theoretical framework of acceptability.Participants A sample of 20 syncope patients recruited to the ASPIRED RCT and 10 healthcare professionals who had a direct care provider and clinical decision role for syncope patients (eg, consultants, junior doctors, advanced nurse practitioners, advanced care practitioners, emergency nurse practitioners and physician associates) were recruited from four hospitals (two in England and two in Scotland) between February 2023 and January 2024.Results Three overarching themes developed that mapped to six of the seven constructs within the theoretical framework of acceptability. The themes were: (1) Efficacy: Patients and healthcare professionals felt that the remote intervention would increase patient reassurance. Healthcare professionals perceived the intervention would improve clinical care pathways by overcoming delays for Holter monitors, but that a standard protocol would be required to ensure appropriate intervention use. (2) Burden: Patients considered that the device was non-obstructive and easy to use. However, healthcare professionals noted that although attaching the device was simple, there would be associated time and resource costs (eg, documentation). (3) Communication and education: Comprehensive verbal and written information were considered necessary to ensure that the intervention was usable by, and acceptable to, patients. Healthcare professionals suggested additional training would be required. Additionally, they considered that feedback from patient monitoring would reinforce their decision-making and improve healthcare professionals’ self-efficacy to use the device appropriately.Conclusions An immediate, enhanced (14-day) ambulatory ECG monitoring patch was positively received by patients and offered healthcare professionals an acceptable route for monitoring emergency department patients with unexplained syncope. However, future use should be controlled using standardised pathways to prevent inappropriate use.Trial registration number ISRCTN10278811.